MicroRNA-146a and Forkhead box protein 3 expressions in nonsegmental vitiligo: an insight into disease pathogenesis - Arwa M Hassan; Yomna M. El-Hamd Neinaa; Amal S El-Bendary; Soha S Zakaria (Wolters Kluwer Medknow Publications, 2019)
Background Autoimmune destruction of melanocytes is the principal hypothesis in vitiligo pathogenesis. MicroRNA-146a (miRNA-146a) is considered an essential regulator of posttranscriptional gene expression, suggesting a potential role in autoimmune diseases. Forkhead box protein 3 (Foxp3) is a crucial transcription factor that controls regulatory T cells, which play a critical role in avoiding autoimmunity. Objective To evaluate the possible role and relationship of miRNA-146a and Foxp3 in the pathogenesis of nonsegmental vitiligo. Patients and methods A total of 50 patients with nonsegmental vitiligo and 25 healthy controls were enrolled in this study. History taking and thorough general and dermatological assessments of vitiligo patients were done including evaluation of Vitiligo Area Scoring Index and Vitiligo Index of Disease Activity scores. Relative levels of miRNA-146a and Foxp3 expressions were analyzed in the peripheral blood mononuclear cells of all participants by real-time reverse transcriptase-PCR. Results The relative levels of miRNA-146a expressions showed significant upregulation, whereas that of Foxp3 showed significant downregulation, in patients with vitiligo compared with healthy controls. In patients with vitiligo, there was negative correlation between relative levels of miRNA-146a and Foxp3 expressions. Furthermore, vitiligo activity assessed by Vitiligo Index of Disease Activity score correlated positively with miRNA-146a expressions and negatively with Foxp3 expressions. However, no significant correlation between their expressions and disease severity assessed by Vitiligo Area Scoring Index score was detected. Conclusion Both miRNA-146a and Foxp3 may be implicated in the pathogenesis and progression of nonsegmental vitiligo. Furthermore, they may serve as potential therapeutic targets for vitiligo.